Idiopathic Normal-Pressure Hydrocephalus: Diagnostic Accuracy of Automated Sulcal Morphometry in Patients With Ventriculomegaly. Issue 4 (22nd May 2019) - Kuchcinski, Grégory; Jacquiez, Caroline; Baroncini, Marc; Machuron, François; Béhal, Hélène; Dumont, Julien; Lopes, Renaud; Delmaire, Christine; Lebouvier, Thibaud; Bottlaender, Michel; Bordet, Regis; Defebvre, Luc; et al.
Abstract: BACKGROUND: Idiopathic normal-pressure hydrocephalus (iNPH) is a treatable cause of gait and cognitive impairment. iNPH should be differentiated from ventriculomegaly secondary to brain atrophy to choose the best therapeutic option (ventriculoperitoneal shunt vs medical management). OBJECTIVE: To determine the diagnostic accuracy of automated sulcal morphometry to differentiate patients with iNPH from patients with ventriculomegaly of neurodegenerative origin. METHODS: Thirty-eight consecutive patients with iNPH (shunt responsive n = 31, nonresponsive n = 7), 35 with vascular cognitive disorder, and 25 age- and sex-matched healthy controls were prospectively included and underwent cognitive evaluation and 3T brain magnetic resonance imaging. Sulcal opening of 10 sulci of interest was retrospectively measured using an automated surface-based approach from the 3-dimensional T1-weighted images. Receiver-operating characteristic curve analyses determined the best parameter to identify iNPH patients. RESULTS: The best parameter to discriminate shunt-responsive iNPH from patients with vascular cognitive disorder and healthy controls was the ratio between calcarine sulcus and cingulate sulcus opening with an area under the curve of 0.94 (95% CI: 0.89, 0.99). A cut-off value of 0.95 provided the highest sensitivity (96.8%) and specificity (83.3%). CONCLUSION: This preliminary study showed that automated sulcal morphometry may help the neurosurgeon to identify iNPH patients and to exclude other causes of ventriculomegaly.